2010
DOI: 10.1021/es1014423
|View full text |Cite
|
Sign up to set email alerts
|

Catechol and Humic Acid Sorption onto a Range of Laboratory-Produced Black Carbons (Biochars)

Abstract: Although the major influence of black carbon (BC) on soil and sediment organic contaminant sorption is widely accepted, an understanding of the mechanisms and natural variation in pyrogenic carbon interaction with natural organic matter (NOM) is lacking. The sorption of a phenolic NOM monomer (catechol) and humic acids (HA) onto BC was examined using biochars made from oak, pine, and grass at 250, 400, and 650 degrees C. Catechol sorption equilibrium occurred after 14 d and was described by a diffusion kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
224
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(244 citation statements)
references
References 43 publications
15
224
1
4
Order By: Relevance
“…Sobek et al (2009) showed that biochars could adsorb organic matter and protect it from being utilised. In this study, the lower soil mineralisation rates in the treatments with biochars produced at higher temperatures than at lower temperatures might be partly attributable to their higher surface areas with greater adsorption affinity for natural organic matter (Kasozi et al 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Sobek et al (2009) showed that biochars could adsorb organic matter and protect it from being utilised. In this study, the lower soil mineralisation rates in the treatments with biochars produced at higher temperatures than at lower temperatures might be partly attributable to their higher surface areas with greater adsorption affinity for natural organic matter (Kasozi et al 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Other researchers have suggested that biochar benefits microbial communities by enhancing the physical and chemical soil characteristics (Lehmann and Joseph 2009;Atkinson et al, 2010;Jindo et al, 2012), providing suitable habitats for microorganisms that protect them from predation (Pietikäinen et al, 2000), supplying labile C substrates for degradation (Thies and Rillig, 2009;Smith et al, 2010), enhancing the availability of macro-nutrients such as N and P (Atkinson et al, 2010;Lammirato et al, 2011), or sorbing compounds that would otherwise inhibit microbial growth (Kasozi et al,2010). To date, these mechanisms have been poorly studied and are mainly discussed in terms as possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changing the mobility of metal(loid)s in soils, the blocking capacity of iron plaque, root-to-shoot translocation in the plant, and the accumulation of metal(loid)s in rice shoot were influenced by biochar amendments . Different types of biochars from various parent materials exhibit quite different properties (Kasozi et al 2010). However, it remains unknown to what extent different biochars can influence translocation and accumulation of metal(loid)s in wheat (an upland crop) grown in a historically contaminated soil containing multiple metals and As.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of biochars from various parent materials exhibit quite different properties (Kasozi et al 2010). However, it remains unknown to what extent different biochars can influence translocation and accumulation of metal(loid)s in wheat (an upland crop) grown in a historically contaminated soil containing multiple metals and As.…”
Section: Introductionmentioning
confidence: 99%